CAPACITY BUILDING CIVITAS AKADEMIKA STAI AL HUSAIN DALAM PEMANFAATAN SISTEM INFORMASI AKADEMIK - Nur Latifah; Fatkhul Ngali (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2021)
Good academic civitas data processing will make the reporting needed by the appropriate database to process policies such as national diploma numbering (PIN), this is very much required to minimize cases of diploma forgery that are rife, to complete and report appropriate civitas data, there must be optimal facilities, infrastructure, and resources. The purpose of this service is to find out the optimization of data processing for the STAI Al Husain academic community with the educational information system (SIAKAD) through mentoring activities with the ABCD approach, and this approach is to empower existing assets. In carrying out an ABCD-based approach, we must look for the availability of assets and synchronization with the academic community's role to measure the success of ABCD. The academic community's data processing and reporting activities have produced results, such as the data are appropriate, and the reporting is applicable. However, they still find the role of the community who still do not understand well about Siakad and still need assistance